Increasing knowledge of Antarctic biodiversity: new endemic taxa of tardigrades (Eutardigrada; Ramazzottiidae) and their evolutionary relationships. Issue 6 (18th August 2019) - Guidetti, Roberto; Massa, Edoardo; Bertolani, Roberto; Rebecchi, Lorena; Cesari, Michele
Abstract : The underestimation of biodiversity and scarce knowledge of the biogeographic distributions of terrestrial meiofaunal component limit our understanding of the origin of Antarctic fauna. One of its main components is tardigrades; nonetheless studies on tardigrade diversity are still few in the continental Antarctic area. In order to increase our knowledge of the underreported terrestrial meiofaunal communities within continental Antarctica, as well as to provide new information for biogeographic and evolutionary analysis of these communities, the tardigrade diversity of 11 samples collected along the coast of Victoria Land was considered. The application of an integrative approach in which morphological (Light – LM, scanning electron – SEM, and confocal laser scanning microscopy – CSLM) and molecular analysis (18S, 28S, cox1 genes) were combined allowed us to characterize the tardigrade fauna inhabiting mosses, lichens, and cyanobacterial mats of Victoria Land. These analyses allowed the detection of two tardigrade species new to science ( Cryoconicus antiarktos sp. nov., Ramazzottius sabatiniae sp. nov.), and the emendation of known species (( Hebesuncus ryani Dastych and Harris, 1994, Ramazzottius nivalis Dastych, 2006, Cryoconicus ljudmilae comb. nov. (Biserov, 1997/98), and Cryoconicus cataphractus (Maucci, 1974)), together with the genus Cryoconicus . The Ramazzottius type of claws was redefined identifying three subtypes. Also, we investigated the phylogenetic position of some problematic/unresolved lineages all belonging to the family Ramazzottiidae. These data increased the knowledge of the biodiversity in Victoria Land, the number of endemic tardigrades in Antarctica, and provided evidence on the origin of Antarctic endemism. Lastly, new methods for integrative taxonomic studies on tardigrades were presented and discussed.